2016
DOI: 10.1104/pp.16.00530
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins Are Initial Targets of Light in the Control of Bud Outgrowth

Abstract: Bud outgrowth is controlled by environmental and endogenous factors. Through the use of the photosynthesis inhibitor norflurazon and of masking experiments, evidence is given here that light acts mainly as a morphogenic signal in the triggering of bud outgrowth and that initial steps in the light signaling pathway involve cytokinins (CKs). Indeed, in rose (Rosa hybrida), inhibition of bud outgrowth by darkness is suppressed solely by the application of CKs. In contrast, application of sugars has a limited effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 102 publications
(168 reference statements)
11
105
1
1
Order By: Relevance
“…Consistent with this, in Arabidopsis dormant buds CK signaling is reduced, and in other species CK levels have also been reported to be reduced relative to active buds (Turnbull et al, 1997; Dun et al, 2012; Roman et al, 2016). Consistently, four genes encoding F-box proteins that promote the ubiquitination and degradation of ARR factors [ KISS ME DEADLY ( KMD )1-4] are bud dormancy genes.…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with this, in Arabidopsis dormant buds CK signaling is reduced, and in other species CK levels have also been reported to be reduced relative to active buds (Turnbull et al, 1997; Dun et al, 2012; Roman et al, 2016). Consistently, four genes encoding F-box proteins that promote the ubiquitination and degradation of ARR factors [ KISS ME DEADLY ( KMD )1-4] are bud dormancy genes.…”
Section: Discussionsupporting
confidence: 63%
“…7A). As previously mentioned in the literature, cytokinin content is well related to IPT3 gene expression which encodes a key enzyme in cytokinin biosynthesis (Tanaka et al, 2006;Barbier et al, 2015;Roman et al, 2016). Furthermore, the slow-down of axis II elongation caused by high concentration of asparagine (30 mM) combined with sucrose ( Fig.…”
Section: Asparagine and Sugars Are Involved In Axis II Nutrition And mentioning
confidence: 58%
“…We also tested the effect of 1 μM and 10 μM of a synthetic form of cytokinins (6-Benzylaminopurine, BAP, in 6% v/v DMSO) and of 10 μM of LGR-991, an inhibitor of cytokinin perception acting as a competitor of the cytokinin receptors Arabidopsis Histidine kinase (AHK4 and AHK3; Spíchal et al, 2009). A previous study in rose has shown that this inhibitor can be used up to 1 mM in planta with no toxic effect (Roman et al, 2016). About 15 nodes were cultivated in the same Petri dish, that constitute one of the three technical repetitions for each biological repetition (n = 3).…”
Section: In Vitro Culture In Solid Mediummentioning
confidence: 99%
See 2 more Smart Citations